2021
DOI: 10.1590/1678-992x-2019-0305
|View full text |Cite
|
Sign up to set email alerts
|

Saponin production from Quillaja genus species. An insight into its applications and biology

Abstract: Quillaja genus (Quillajaceae family) is endemic to South America, where is represented by two species, Quillaja saponaria and Quillaja brasiliensis. One outstanding characteristic of these forest tree species is their production of saponins, a family of amphipathic glycosides, involved in the defensive response of plants against biotic and abiotic factors. Saponins are metabolites of economic importance due to their chemical and physical properties. Basic and applied research efforts performed during the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The soap bark tree belongs to the order Fabales and family Quillajaceae (Guerra & Sepulveda, 2020). This tree is native to China, Peru, and Chile (Angeles Jr., Gallego, Navarro, & Chien, 2017; Francis et al, 2002).…”
Section: Plant Extracts Used In the Control Of Tilapia Reproductionmentioning
confidence: 99%
“…The soap bark tree belongs to the order Fabales and family Quillajaceae (Guerra & Sepulveda, 2020). This tree is native to China, Peru, and Chile (Angeles Jr., Gallego, Navarro, & Chien, 2017; Francis et al, 2002).…”
Section: Plant Extracts Used In the Control Of Tilapia Reproductionmentioning
confidence: 99%
“… 21 These intricate natural products consist of a hydrophobic triterpene core, an aliphatic sidechain, and complex, defined carbohydrate functional groups. In the quest for alternative manufacturing methods, semi-synthetic chemistry, biochemistry 22 , 23 , 24 , 25 , 26 , 27 and agricultural plant microculture or sapling microfarming 28 , 29 have been explored. A key breakthrough was recently made by identifying the crucial enzymatic pathways involved in the synthesis of QS-21-related immune modulatory saponins.…”
Section: Introductionmentioning
confidence: 99%
“…These biological effects lead to the induction of an innate and adaptive immune response, including cellular and humoral types [ 20 ]. High-grade quillaja extracts containing ≥90% w / w saponins (dry basis) can be employed as immunostimulant agents (vaccine adjuvants) in veterinary and human vaccine formulations [ 20 , 21 ], where they effectively modify the activities of antigen-presenting cells (macrophages and dendritic cells). It has been demonstrated that quillaja saponins, alone or incorporated into immune-stimulating complexes (ISCOMs), modulate immunity responses in different ways: by increasing antigen uptake in antigen-presenting cells (APC), by stimulating Th1 and Th2 immune responses to different antigens, and by inducing cytotoxic T lymphocytes (CTL) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%